Increasing Sales Through E-Commerce for MSMEs BTPN Syariah Pasar Kliwon District, Surakarta City - Candraningtyas, Callista Vania; M. Taufiq; Oktafia, Renny (PT Inovasi Pratama Internasional, 2024)
MSMEs are important in advancing the economy in Indonesia today, even though they still face various challenges, one of which is a lack of market access. To overcome this challenge, it is important for MSME players to utilize digital technology that has developed, such as e-commerce. Bank BTPN Syariah has created mentoring programs such as the Friends of Power program through accompanying facilitators from Certified Independent Study Internship (MSIB) participants. The aim of this activity is to determine the income growth of Micro, Small and Medium Enterprises (MSMEs) and develop their businesses in Pasar Kliwon District. The method used is the ABCD (Asset Based Community Development) method, which is a design for community empowerment using assets and data collection techniques through observation and documentation. This shows that the use of digital technology, especially e-commerce, can have a significant impact in developing their business and increasing the income of MSME customers of BTPN Pasar Kliwon District.